If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2x + 2) = 24 Reorder the terms: 3(2 + 2x) = 24 (2 * 3 + 2x * 3) = 24 (6 + 6x) = 24 Solving 6 + 6x = 24 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 6x = 24 + -6 Combine like terms: 6 + -6 = 0 0 + 6x = 24 + -6 6x = 24 + -6 Combine like terms: 24 + -6 = 18 6x = 18 Divide each side by '6'. x = 3 Simplifying x = 3
| 3x-5=7x+9 | | 3(2*1)=5(x-8) | | 5x=2-1x | | 2x^2-1x=28 | | 8-40-112=0 | | 2c=e(j+m) | | 3x+7=2+x | | y=2(0)+10 | | x-6=24 | | y=-3(0)-12 | | 6-9x=72-30x | | 4(k-3)=3(k+1) | | -3(3s-2)-6=-3(5s+3)-5 | | -8w(2)+8w+30= | | M=-3n-2 | | 5(v+1)=3(v+11) | | t=.25*150+40 | | R=4-6+5 | | -(1+8v)+3v=14-8v | | n=4*60-160 | | -3(2s-5)-15=-2(9s+8)-3 | | 196=14(8a-2) | | 25(1+3g)=400 | | -10=3b-2b | | 61-4x=10x-19 | | 3(2fg+4)= | | 24=12(3-w) | | x-9=-4 | | 0.55x+.05(4-x)=.10(-68) | | 4(10t-7)= | | 6x-7(0)=12 | | 18k-3(4k+5)= |